Cash-on-Hand and the Duration of Job Search: Quasi-Experimental Evidence from Norway. - Christoph Basten; Andreas Fagereng; Kjetil Telle (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
We identify the causal effect of lump-sum severance payments on non-employment duration in Norway by exploiting a discontinuity in eligibility at age 50. We find that a severance payment worth 1.2 months' earnings at the median lowers the fraction re-employed after a year by six percentage points. Data on household wealth enable us to verify that the effect is decreasing in prior wealth, which favors an interpretation as liquidity constraints over the alternative of mental accounting. Finding liquidity constraints in Norway, despite its equitable wealth distribution and generous welfare state, means they are likely to exist also in other countries.
Keywords: C41; E24; J65; 330